Stockholm Concert Database - Reese Willén, Anne (Uppsala University, 2024)
This database has been produced for the project "Canon and Concert Life: Formation Processes within Stockholm's Music Life 1848-1914" (financed by the Riksbankens Jubileumsfond). The data comprises information about concerts and concert repertoire in Stockholm during the period 1848-1908. Data has been recorded for every tenth year during this period. For each year, as much data as possible has been collected regarding public music activities in the city. The main source material has consisted of digitized Swedish newspapers. The material has been manually reviewed by Anne Reese Willén, and all information discovered about public music performances has been recorded in the database. The database is structured around individual musical events and includes metadata about actors (concert organizers, musicians, composers, and institutions/organizations), information about actors (nationality, instrument, gender, birth/death years, profession, composition activity, other information, etc.), repertoire (composers and works), concert venue, time, date, ticket price, ticket sales, references to sources (concert advertisements, reviews, notices) etc. The database is also linked to the website, presenting various types of data analysis, information visualization, and additional search functionality.

Denna databas har producerats för projektet "Kanon och konsertliv: Formeringsprocesser inom Stockholms musikliv 1848-1914" (finansierat av Riksbankens jubileumsfond). Datat innehåller information om konserter och konsertrepertoar i Stockholm under perioden 1848-1908. Data finns registrerat för vart tionde år under perioden. För varje år har så mycket data som möjligt samlats in kring offentliga musikaktiviteter i staden. Det huvudsakliga källmaterialet har utgjorts av digitaliserade svenska dagstidningar. Materialet har granskats manuellt av Anne Reese Willén och all information som upptäckts om offentliga musikframträdanden har registrerats i databasen. Databasen är uppbyggd kring enskilda musikhändelser och inkluderar metadata om aktörer (konsertarrangör, musiker, tonsättare och institutioner/organisationer), information om aktörer (nationalitet, instrument, kön, födelse/dödsår, yrke, kompositionsaktivitet, annan information mm), repertoar (tonsättare och verk), konsertlokal, tid, datum, biljettpris, biljettförsäljning, referenser till källor (konsertannonser, recensioner, notiser mm). Databasen är även kopplad till hemsidan som presenterar olika typer av dataanalys, informationsvisualisering och andra sökfunktioner i databasen.
Stockholm Concert Database
Keywords: music research; musikforskning; musical performances; musikframträdanden; history of music; musikhistoria; music market; musikmarknaden; art music; konstmusik; musicians; musiker; music culture; musikkultur; arrangers (occupations); arrangörer (musik); concert activity; konsertverksamhet; music sociology; musiksociologi; light music; underhållningsmusik; music programmes; musikprogram (media); music life; musikliv; popular music; populärmusik; instrumental music; instrumentalmusik; concert programmes (hand-outs); konsertprogram (programblad); Cultural activities and participation; Kulturaktiviteter och deltagande; Musicology; Musikvetenskap; Society; Samhälle och kultur